Municipal Sewage Sludge Composting in the Two-Stage System: The Role of Different Bulking Agents and Amendments - Dorota Kulikowska; Katarzyna Bernat; Magdalena Zaborowska; Magdalena Zielińska (Energies, 2022)
This study assessed the effect of different lignocellulosic amendments and bulking agents on compost stability (based on a 4 day respiration activity test, AT4, and self-heating factor, SHF) and maturity (based on the nitrification index Initr and the ratio of C in humic acids, HA, to total organic carbon, TOC, in compost, CHA/TOC). With all feedstock compositions (FCs), the share of sewage sludge was 79% (wet mass). For FC1, wood chips (13.5%) and wheat straw (7.5%) were used as bulking agents and amendments; for FC2, instead of wood chips, energy willow was added; for FC3, pine bark (13.5%) and conifer sawdust (7.5%) were used. All FCs produced stable and mature compost; however, with FC2, the thermophilic phase last 3 days longer than with the other FCs. Moreover, an AT4 value below 10 g O2/kg dry mass (d.m.) was obtained the earliest with FC2 (after 45 days, ca. 15–20 days earlier than with other FCs). With FC2, Initr below 0.5 was obtained in ca. 60 days, 10 days earlier than with FC3 and 30 days earlier than with FC1. The highest net increases in HS (86.0 mg C/g organic matter (OM)) and HA (56.3 mg C/g OM) were also noted with FC2; with other FCs, the concentrations of these compounds were from 1.3- to 1.5-fold (HS) and from 1.4- to 1.9-fold (HA) lower. With FC2, the highest CHA/TOC (15.5%) was also noted, indicating that this compost contained the largest share of the most stable form of organic carbon. The rates of OM removal in the bioreactor ranged from 7.8 to 10.1 g/(kg d.m.·day). The rates of SH and HA formation ranged from 1.63 to 4.83 mg C/(g OM·day) and from 1.23 to 1.80 mg C/(g OM·day), respectively. This means that, through the choice of the amendments and bulking agents, the length of the composting time needed to obtain a stable and mature product can be controlled.